Improvisation of Round Robin Algorithm (International Journal of Innovative Research in Computer Science & Technology, 2022)
We are trying to improvise the existing  Round Robin Algorithm and test its performance across  host OS and VM as well. We would be testing the  performance of the improvised algorithm on the Cent OS  running on Virtual Box..  We have worked on the scheduling algorithm specifically  Round Robin Scheduling in our lab classes. Basically, we  will be finding out the best way to properly select the “Time  Quantum” so as to get Minimum ‘Waiting Time’ and  ‘Turnaround Time’.After looking into so many research papers, we have found  that, by sorting the processes in increasing order of their  burst time and taking median of all the burst time, we can  minimize the waiting and turnaround time.
Keywords: Round Robin; Cent OS; Waiting Time; Time Quantum; Turnaround Time